Interacciones multimodales en una clase de español de octavo año costarricense - Flores Solano, Carol (Universidad de Costa Rica, 2021)
This research carries out a multimodal analysis of the genres used in the Spanish class by a teacher at the Canadian International School in Costa Rica, together with the semiotic modes and their metafunctions within each of the generic phases. It is a qualitative, descriptive approach and corresponds to a case study. The corpus is constituted by the video recordings of the teacher's pedagogical mediation directed to a population of eight eighth grade students in this educational center. The analysis focuses exclusively on the figure of the teacher and excluded the participation of the students, in order to guarantee their anonymity. The results indicate the presence of five genres: student work, revision, joint reading, school interview and teacher exposition. As modes, orality, writing, graphic resources, gestures, body movements and displacement were identified as transversal to all of them. As conclusions, this study suggests rethinking the Spanish class not as "typically linguistic" but as modally diverse, that is, articulated by multiple semiotic modes, all of which intertwine during mediation. Furthermore, it suggests that such a label may be related to the predominant use of writing in the nuclear phases of the genres.